CONTEMPORARY CONCEPTIONS OF THE TERM “EMPLOYER” - Dragićević, Marija (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
As a rule, contemporary labour law provides the definition of the term “employer”. While the reason for defining the concept of “employee” is the need to determine labour legislation field of application, the essence of providing legal definition of the term “employer” is to identify the entity that is responsible for fulfilling obligations to employees and other engaged individuals or their unions and other institutions of representation. Despite the importance of providing an accurate definition, comparative labour legislation can barely offer a classification of the term “employer” which indicates that the legislation bodies have managed to overcome (the circular) definition of idem per idem. Additionally, the present definitions are not adjusted to triangular (and multilateral) labour-generated relations. Consequently, in order to harmonize the legal framework with the changes which occur in economic reality, more and more labour law systems initiate the process of introducing new legal model of plural-employer. Therefore, the author of the paper firstly analyzes the need to re-conceptualize the term “employer” and studies (current) unitary and (new) plural-employer conceptions of this term. Finally, using the example of digital platforms, the author demonstrates inadequacy of the existing legal definitions of the concept “employer” and emphasizes the need for adopting the new ones.
Keywords: employer; unitary; single-employer; plural-employer; conception